Soccer syndrome - 2: Common innominate malalignments and its manual diagnostic techniques in pelvic malalignments syndrome - Elumalai, G.; Declaro, M.; Sanyal, S.; Bench Bareng, M.; Mohammad, A. (American Journal of Sports Science, 2015)
The innominate malalignments are most common in sports injuries and even in every client who presents with low back & pelvis pain or dysfunction. In this study, we used simple bony palpation method to assess the various innominate malalignments in football players, which was fails to observe in previous work of various authors. While there are many methods to determine pelvic symmetry or asymmetry, this method is very simple one and that consistently works well for me. This study includes the healthy football players from National Football Club (NFC) of our institution, who were training or playing during the period of investigation (September 2014 - May 2015) (n = 40) were eligible for participation. At entry to the study, this eligible sample had a mean age of 22.2 ± 3.9 years, height of 175.8 ± 6.6 cm, and mass of 87.5 ± 7.1 kg. The number of eligible participants at each time point was 40 for all the four session time, point 1 (T1; start of preseason-3) and point 2 (T2; end of season-3). Subjects were limited to men who had a normal muscle strength and Range of Motion (ROM) of the back and lower extremities and who had no history of orthopaedic or neurologic disorders. All the individuals are subject to gain access the malalignment of both Innominate bones of the bony pelvis unit. In addition, to justify our diagnosis we access the muscles of the functional slings and the muscles around the bony pelvis. The techniques were repeated in different position and also performed for two times per day and continued for fifteen days to standardize. In this study, we observed, 92.5% i.e., the majority of the soccer's are suffering with multiple innominate malalignments. The soccer's suffering with single component malalignment account for about 25% includes the isolated Rotational, Upslip or Tilt innominate stucks and soccer's who had the normal innominate at the end of the season is only about 7.5%. Conclusion: This method of assessing the pelvic malalignments until then not documented. In this sense, the objective of this study is to analyze and document the different presentations in pelvic malalignments which are common in soccer players and its simple method of evaluation is the literature state of the art. The present study may provide useful information to analyze common presentations of pelvic malalignments in different sports.